Retrospective examination of home healthcare services applications in a children's hospital - Ökkeş Kısa; Tanju Çelik; Aynur Uysal Toraman (SERNEV, 2023)
Introduction: The purpose of the present study was to examine the descriptive data regarding the children, their families, and living conditions in the records of home healthcare services provided for children between 01.04.2020 and 01.04.2021 at a children's university hospital.Methods: The sample of this descriptive study consisted of the files of 170 pediatric patients who received service from Health Sciences University (SBU) Izmir Dr. Behçet Uz Pediatric Diseases and Surgery Training and Research Hospital Home Healthcare Services Unit between 01.04.2020 and 01.04.2021. The data were collected with the Data Record Form that was created by the researchers in line with the contents of the files kept for patients. The analysis of the data in this form was made in the SPSS package program 25.0 trial version. The data were described in terms of numbers, percentages, and averages, and the Chi-Square Significance Test was used in the comparisons made between the demographic data. The statistical significance level was considered as p lt;0.05. To conduct the study, permission was obtained from the Ethics Committee of S.B.U. Izmir Dr. Behçet Uz Pediatric Diseases and Surgery Training and Research Hospital.Results: The children who were included in the study were between the ages of 0 and 17 and the average age was 9.11±4.61. It was found that a total of 54.7% of the children were male, 97.6% were cared for by their mothers, 61.8% of the children whose files were examined had social security at the Social Security Institution (SSI), 51.8% were receiving service from the unit and were diagnosed with a neurological disease, and 58.8% were fully dependent in their daily living activities, 27.1% of them used mechanical ventilation, 37.6% used aspirator devices, 37.1% needed Oxygen (O2) support, 48.7% were fed orally, 27.7% were fed through the nasogastric route, and 23.6% were fed through Percutaneous endoscopic gastrostomy (PEG) and 4.2% of the participating children developed pressure sores. According to the records regarding the physical conditions of the places where children lived, 72.4% lived in apartments, 38.8% had a house that was heated by a heating system natural gas, 98.8% had good lighting in their homes, and 57.1% had alaturka toilet in their homes. Also, 64.8% of the children stayed in the living room of the house and 92.4% had good home hygiene. A statistically significant difference was detected between the income status of the children's families and their social security (X2= 47.542 p=0.001, df=1).Conclusion: The factors such as the majority of patients registered to home healthcare services being cared for by their mothers, their high rates of dependency in daily living activities, some developing pressure sores, the need to be attached to a medical device, and varying home conditions in suitability for care show that patients have varying medical, psychological and social needs. For this reason, it would be beneficial to focus on pediatric studies in home healthcare services, organize.